Clinical researchSerum neutrophil gelatinase-associated lipocalin as a marker of kidney function in pregnancy – useful or doubtful? - Małyszko, Jacek S.; Rams, Leszek; Drozdowska-Rams, Lena; Małyszko, Jolanta (Archives of Medical Science, 2010)
Introduction : The aim of the study was to assess whether neutrophil gelatinase-associated lipocalin (NGAL) and cystatin C could reflect kidney function in pregnant healthy women. Material and methods : The studies were performed on 130 healthy pregnant women (n = 63, 3rd trimester; n = 21, 2nd trimester; n = 46, 1st trimester) and 30 healthy female volunteers. Serum NGAL, cystatin C, IL-6, and hs-CRP were assayed using commercially available kits. Results : Serum cystatin C rose steadily during the pregnancy, whereas NGAL rose in the 2nd trimester, then decreased in the 3rd trimester. In univariate analysis, NGAL correlated with serum cystatin C, number of pregnancies, white blood cell count, total iron-binding capacity (TIBC), ferritin, and IL-6, and tended to correlate with eGFR. In multiple regression analysis the only predictor of serum NGAL was cystatin C. Conclusions : Serum NGAL in pregnancy might reflect subclinical inflammation rather than kidney function. It seems that NGAL, similarly to cystatin C, is not useful to monitor renal function in pregnancy.